Fluid Dynamic Analysis of Shaken and Mechanically Stirred Reactors by Means of Optical Techniques - Pieralisi, Irene <1987> (Alma Mater Studiorum - Università di Bologna, 2016)
This research aims at deepening the knowledge of the hydrodynamics developing within some specific mixing system configurations. In particular, a standard geometry stirred vessel, an unbaffled stirred vessel of unconventional geometry and a shaken bioreactor are studied. Optical techniques (LDA, PIV) are employed in order to obtain detailed information on the mean and turbulent characteristics of the flow developing within the different lab-scale reactors, while subsequent data analysis addresses the comprehension of the principal macro and micro phenomena occurring in the flow. When studying the standard geometry stirred reactor, the evolution of trailing vortices on the wake of a PBT turbine is investigated for the first time under laminar regime. A three-dimensional characterization of the vortical structures is carried out in terms of vorticity levels and locus. The second case study regards an unbaffled stirred tank of low liquid height-to-tank diameter ratio. Due to the unconventional geometry of the system, peculiar interactions arise between the strong tangential motion of the flow, the impeller discharge stream and the flow free surface. Big efforts are devoted to the characterization of this phenomenon which strongly influences the flow, and a mathematical model able to predict it is sought for. In the last part of this research, the operation of shaken bioreactors is explored. Particularly, the suspension dynamics occurring in the presence of solids within a flat-bottomed cylindrical system are investigated, and the associated two-phase flow is assessed by means of 2D-PIV. Also, the influence of a conical bottom on the single-phase flow is examined. A comparative study of the different bioreactors typologies allowed to identify interesting affinities never detected before in the fluid dynamic behaviour of unbaffled stirred tanks and shaken bioreactors, revealing that these two types of reactors can induce very similar flows, although being technologically very different.